Hubungan Kualitas Tidur dengan Prestasi Belajar Mahasiswa Angkatan 2017 Fakultas Kedokteran Universitas Kristen Indonesia - Rahayu Yekti; Raudendy Rambe (Pro-Life, 2021)
Sleep is one of human physiological needs. Adequate sleep has an important role in improving cognitive skills, especially memory storage. Poor sleep quality will result in daytime sleepiness which will affect the physical health and cognitive function of students and have an impact on their academic performance. The purpose of this study was to determine the relationship between sleep quality and the cumulative achievement index (GPA) in students of the Faculty of Medicine, Universitas Kristen Indonesia. Methods: observational analytic research with a cross sectional approach, which was carried out during June 2020 - June 2021. Sampling used a purposive sampling technique from 119 respondents using a PSQI questionnaire that matched the inclusion and exclusion criteria, then the data were analyzed using the SPSS computer program. The results of the study showed good sleep quality with good learning achievement, 36 students (30.2%), poor sleep quality with good learning achievement, 82 students (68.9%), univariate data. Bivariate analysis of Chi-square statistical test obtained p value = 0,508 > alpha value (0.05). The conclusion that there is no relationship between sleep quality and learning achievement in students of the Faculty of Medicine Universitas Kristen Indonesia class of 2017. However, it is hoped that students can further improve the quality of sleep because it greatly impacts student health and improves cognitive function so that the learning achievement of students of the Faculty of Medicine, Indonesian Christian University, generation can be further improved.